2010
DOI: 10.1111/j.1464-410x.2010.09341.x
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant carcinoma in situ and tumour size are prognostic factors for bladder recurrence after nephroureterectomy for upper tract transitional cell carcinoma

Abstract: grade, concomitant upper tract carcinoma in situ (CIS), and size were all analysed. Univariate and multivariate analyses were done using the Kaplan-Meier Method, with the log-rank test, and the Cox proportional hazards regression model, respectively. RESULTSThe median follow-up was 71 months, during which bladder tumours were detected in 42 patients (54%). On univariate analyses, tumour stage ≥ pT2 ( P = 0.015), concomitant upper tract CIS ( P = 0.001), high-grade tumour G3 ( P = 0.027) and tumour size > 4 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 26 publications
4
25
2
5
Order By: Relevance
“…We found that presence of CIS is a risk factor for the development of invasive/multicenteric bladder cancers in bivariate analysis. This is in agreement to what was reported by Pieras et al [13] and Wheat et al [14] .…”
Section: Discussionsupporting
confidence: 94%
“…We found that presence of CIS is a risk factor for the development of invasive/multicenteric bladder cancers in bivariate analysis. This is in agreement to what was reported by Pieras et al [13] and Wheat et al [14] .…”
Section: Discussionsupporting
confidence: 94%
“…It is related to tumor recurrence, with 7-fold increase risk in finding tumors after transurethral resection and BCG treatment. Tumor size has also been used as a criteria to proceed with more aggressive treatment in pT1-stage bladder cancer (23,24). Negative expression of this catenin has been related to worse prognosis, tumor stage, tumor grade and UC disease recurrence in other studies (11,25).…”
Section: Discussionmentioning
confidence: 99%
“…1 Gender, age and the initial location of the tumor within the upper urinary tract are no longer accepted as prognostic factors. 1 Lymphovascular invasion, [5][6][7] tumor necrosis, 8,9 tumor architecture 10 and concomitant carcinoma in situ 11,12 are associated with higher risks of recurrent disease and cancer-specific mortality. Molecular markers such as microsatellite instabilities, 13 E-cadherin, hypoxia-inducible factor-1a and a telomerase RNA component 14 have been shown to be useful for prognosis, although none of the markers has been externally validated.…”
mentioning
confidence: 99%